Ceramic veneers: a case report - MEHANNA ZOGHEIB, Carina; AFRAM, Antonio; GHALEB, Maroun (International Arab Journal of Dentistry (IAJD), 2020)
Contemporary dentistry’s main aim is to re-establish a patient’s esthetic appearance. In order to achieve this goal, minimal invasive techniques are required such as bleaching, direct composites and indirect ceramic veneer restorations, instead of ceramic crowns. Many problems in the esthetic zone may be resolved with bleaching techniques but the need for an alternative for crowns- when bleaching is impossible to achieve or gives insufficient results- led to the advent of laminate veneers. These techniques may be processed in two different ways: direct or indirect. Direct laminate veneers are prepared in the dental clinic by applying layers of composite material directly to the prepared tooth surface. Indirect laminate veneers may be produced from ceramic materials, in the dental laboratory. In this case report, ceramic veneers were used for a patient with esthetic problems related to cervical abrasion and discolorations on her upper canines and premolars. The preparation and cementation are described step-by-step and the technique discussed. As a conclusion, ceramic veneer restorations may be a treatment option for patients with esthetic problems similar to the one reported in this case.